1967
DOI: 10.1002/j.1551-8833.1967.tb03501.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying Shallow Depth Sedimentation Theory

Abstract: Tests were begun in 1964 to evaluate the efficiency of tube configurations as sedimentation devices and to evaluate means of sludge removal. Preliminary tests with single tubes of various sizes quickly demonstrated that they were efficient sedimentation devices. During these preliminary tests, it was found that the accumulated sludge could be readily removed by periodically draining the tubes, if they were inclined slightly in the direction of flow. An angle of inclination of 5 degrees was found to be adequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

1968
1968
1986
1986

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 2 publications
(2 reference statements)
0
8
0
2
Order By: Relevance
“…In recent years, two American engineers HANSEN and CULP [4,6,7,8] and their asso ciates have reported extensively on the appli cation of shallow depth sedimentation devices. Their design is a collection or bundle of small diameter tubes which follow the models anal yzed in the earlier part of this paper.…”
Section: Deux Ingénieurs Américains Allen Hazenmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, two American engineers HANSEN and CULP [4,6,7,8] and their asso ciates have reported extensively on the appli cation of shallow depth sedimentation devices. Their design is a collection or bundle of small diameter tubes which follow the models anal yzed in the earlier part of this paper.…”
Section: Deux Ingénieurs Américains Allen Hazenmentioning
confidence: 99%
“…Il est commode de considérer x comme étant la distance maximale qu'une particule ayant vitesse de sedimentation V s pourra franchir sans atteindre la paroi du tube Cette distance correspond a une particule dont le particle flux below boundary line/débit solide sous la frontière = c-2 j dz • j u(y, z)dy (8) O jrt particle flux below boundary line /debit solide sous la frontière total particle flux x = 0 / debit solide total a x = 0 F = 1 --(aj8 + sin _1 J 6-2a 3 i?) n (9) 1XV S 8i/R '.…”
Section: -B)unclassified
See 1 more Smart Citation
“…The authors have described 3,5 two basic tube configurations shown in Fig. 1: (a) essentially horizontal and (b) steeply inclined.…”
Section: Basic Tube Configurationsmentioning
confidence: 99%
“…diameter tube, 4 ft long, of 10 min. through which water is passed at a A detailed literature review by the rate of 10 gpm/sq ft of cross-sectional authors 3 showed that there have been area has a Reynolds number of only many attempts at applying the shallow 24, while providing an equivalent surdepth sedimentation principles pro-face overflow rate of 235 gpd/sq ft. posed by Hazen and Camp. Wide, The 3 min detention time of such a shallow trays were generally inserted tube settling device under these condiwithin basins of conventional design.…”
mentioning
confidence: 99%